El efecto de la ineficacia de los actos traslaticios de dominio en el hecho generador del impuesto de alcabala (Tema Central) - Carpio Frixone, María Bernarda (2021)
This work presents a critical evaluation of article 529 of Cootad (Organic Code of Territorial Organization, Autonomy and Decentralization). Article 529 prescribes that the alcabala tax that has been paid for the transfer of a property will not be refunded in cases of reform, nullity, resolution or rescission of the contracts that preceded the transfer. Specifically, this work analyzes the effect that those cases of inefficacy have over the alcabala tax’s taxable event. This analysis is based on the principle of contributory capacity and its incidence over the taxable event of the alcabala tax. It seeks to determine if, in the cases of reform, nullity, resolution or rescission of the acts that preceded the transfer, the taxable event of the alcabala tax is configured. This work concludes that in cases of nullity, resolution or rescission there is no legal justification to deny the refund of the paid alcabala tax, given that the consequence of those cases of inefficacy is to reverse the effects of the act or contract that originated the tax collection. Therefore, we consider that this retroactive effect conduces to the dissolution of the taxable event, so denying its refund contradicts the principle of contributory capacity.